The Soul Eaters
THE SOUL EATERS examines the challenges facing women in Western Africa, who are held responsible for unexplained deaths in their communities, and are accused of engaging in witchcraft and sorcery. In Burkina Faso, a "soul eater" is typically a woman who is past child bearing age, someone who may not have children, or someone who exhibits behavior that is somehow "socially unacceptable." Driven from their villages, often with no place to go, these women are marginalized from society, and many are unable to ever return to their homes.